2015
DOI: 10.1371/journal.pone.0122208
|View full text |Cite
|
Sign up to set email alerts
|

Endopolyploidy Changes with Age-Related Polyethism in the Honey Bee, Apis mellifera

Abstract: Honey bees (Apis mellifera) exhibit age polyethism, whereby female workers assume increasingly complex colony tasks as they age. While changes in DNA methylation accompany age polyethism, other DNA modifications accompanying age polyethism are less known. Changes in endopolyploidy (DNA amplification in the absence of cell division) with increased larval age are typical in many insect cells and are essential in adults for creating larger cells, more copies of essential loci, or greater storage capacity in secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
(54 reference statements)
1
20
1
Order By: Relevance
“…9 In Dinoponera australis, organs related to digestion and excretion present the much higher levels of endopolyploidy when compared with other organs such as brain and muscle. 31 This was also observed in Apis mellifera by Rangel et al, 32 although no statistically significant differences were observed. In addition to differences with regard to other organs, in Apis mellifera, MT showed higher ploidy values in an age-dependent manner.…”
Section: +supporting
confidence: 68%
“…9 In Dinoponera australis, organs related to digestion and excretion present the much higher levels of endopolyploidy when compared with other organs such as brain and muscle. 31 This was also observed in Apis mellifera by Rangel et al, 32 although no statistically significant differences were observed. In addition to differences with regard to other organs, in Apis mellifera, MT showed higher ploidy values in an age-dependent manner.…”
Section: +supporting
confidence: 68%
“…Because age-related endopolyploidy has been reported in worker honeybees (Rangel et al, 2015), it is probably reasonable to expect that the fat body of long-lived individuals will have more endopolyploid cells than others in termites. In fact, queens in eusocial insects including termites exhibit long lives; their lifespan is more than 10-fold longer than that of workers and soldiers (Jemielity et al, 2005;Keller, 1998;Thorne, Breisch, & Haverty, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Endoreduplication is often attributed to increasing cellular size, metabolism, and gene expression owing to the increasing availability of DNA templates for transcription (Bourdon et al, ; Claycomb, Benasutti, Bosco, Fenger, & Orr‐Weaver, ; Edgar et al, ; Galitski, Saldanha, Styles, Lander, & Fink, ; Nagl, ). In social hymenopterans, several studies have shown the intriguing linkage between caste specialization and endopolyploidy (Rangel, Strauss, Seedorf, Hjelmen, & Johnston, ; Scholes, Suarez, & Paige, ; Scholes, Suarez, Smith, Johnston, & Paige, ). Scholes et al () investigated the degree of polyploidy within and among castes of four ant species with worker polymorphism and observed variation in ploidy levels among workers with different body sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Also to be determined are environmental effects on the parameters. Flight performance in honeybees is associated with a reduction in polyploidy with age [19]. Further, while it is known that endocyclic cells are large and metabolically active, have multiple sites of origin firing, and variable levels of transcription [10,14,15], it remains to be seen whether underreplication is a mechanism to meet the metabolic demands of flight with a minimal increase in nuclear size.…”
Section: Discussionmentioning
confidence: 99%
“…The thorax is comprised of a variety of different tissues, including cuticle, gut, tergal depressor of the trochanter (TDT) muscle, and the direct and indirect flight muscle [18]. Of these, only the gut is expected to have any polyploid nuclei, according to data collected from a bee and an ant [19,20]. Yet, gut nuclei are expected to be rare relative to the nuclei from other thoracic tissues, as the thorax is filled by muscle [21].…”
Section: Introductionmentioning
confidence: 99%